2021
DOI: 10.3389/fbioe.2021.653417
|View full text |Cite
|
Sign up to set email alerts
|

Rational Design of Hyaluronic Acid-Based Copolymer-Mixed Micelle in Combination PD-L1 Immune Checkpoint Blockade for Enhanced Chemo-Immunotherapy of Melanoma

Abstract: The application of combinational therapy breaks the limitation of monotherapy and achieves better clinical benefit for tumor therapy. Herein, a hyaluronic acid/Pluronic F68-based copolymer-mixed micelle was constructed for targeted delivery of chemotherapeutical agent docetaxel (PHDM) in combination with programmed cell death ligand-1(PD-L1) antibody. When PHDM+anti-PDL1 was injected into the blood system, PHDM could accumulate into tumor sites and target tumor cells via CD44-mediated endocytosis and possess t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…Checkpoint blockade immunotherapy has emerged as a promising direction in the clinical treatment of CM ( Huang and Zappasodi, 2022 ). Immune checkpoint inhibitors, such as CTLA-4 , PD-1 , PD-L1 , and PD-L2 , regulated the function and inhibited the antitumor immunity of activated T cells ( Zhou et al, 2021 ). In the current study, the IPS result suggested that low-risk score patients displayed a greater response to the anti- CTLA-4 , anti- PD-1 , and anti- CTLA-4 /anti- PD-1 of CM.…”
Section: Discussionmentioning
confidence: 99%
“…Checkpoint blockade immunotherapy has emerged as a promising direction in the clinical treatment of CM ( Huang and Zappasodi, 2022 ). Immune checkpoint inhibitors, such as CTLA-4 , PD-1 , PD-L1 , and PD-L2 , regulated the function and inhibited the antitumor immunity of activated T cells ( Zhou et al, 2021 ). In the current study, the IPS result suggested that low-risk score patients displayed a greater response to the anti- CTLA-4 , anti- PD-1 , and anti- CTLA-4 /anti- PD-1 of CM.…”
Section: Discussionmentioning
confidence: 99%
“…IVT-mRNA is inherently immunogenic, it activates pattern recognition receptors (PRRs) such as Toll-like receptors (TLR-3, TLR-7, and TLR-8) in the endosomal compartments of host cells [184,185]. In some cases, activation of innate immunity by IVT-mRNA is potentially advantageous for vaccines, as it promotes recruitment of DCs to the administra-tion site and subsequent maturation of DCs to elicit potent adaptive immunity.…”
Section: Structural Optimization Of Ivt-mrnamentioning
confidence: 99%
“…Moreover, CUR [180] and rosiglitazone (ROZ) [181] were co-loaded as MDR reversing and adipogenesis agents, respectively. HA-SANPs were also obtained with HA-VES and proposed as nanocarriers for DOX treatment in Adriamycin resistant breast cancer cells [182], as well as for the combined DOX/CUR [183] or DTX/programmed cell death ligand 1 (PD-L1) antibodies (anti-PD-L1) [184] protocols exploiting CUR as coadjuvant and the Anti-PD-L1 as an immune checkpoint.…”
Section: Ha-prodrug Nanoassembliesmentioning
confidence: 99%